The Mixing Problem in Programme Evaluation - Manski, C. F. (Review of Economic Studies, 1997)
A common concern of evaluation studies is to learn the distribution of outcomes when a specified treatment policy, or assignment rule, determines the treatment received by each member of a specified population. Recent studies have emphasized evaluation of policies providing the same treatment to all members of the population. In particular, experiments with randomized treatments have this objective. Social programmes mandating homogeneous treatment of the population are of interest, but so are ones in which treatment varies across the population. This paper examines the use of empirical evidence on programmes with homogeneous treatments to infer the outcomes that would occur if treatment were to vary across the population. Experimental evidence from the Perry Pre-school Project is used to illustrate the inferential problem and the main findings of the analysis. Copyright 1997 by The Review of Economic Studies Limited.